2019
DOI: 10.1159/000503236
|View full text |Cite
|
Sign up to set email alerts
|

Do We Know the True Burden of Tick-Borne Encephalitis? A Cross-Sectional Study

Abstract: Introduction: Tick-borne encephalitis (TBE) is an acute human arboviral infection of the central nervous system caused by a virus that is transmitted to humans mainly by tick bites. TBE is endemic in Europe and has become an increasingly important public health concern in recent years. Cases of TBE in Italy have occurred mainly in the north-east and central parts of the country. Vaccination is recommended for people who live in or visit areas at higher risk of tick bites. Objective: The aim of our study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…On the other hand, Occupational Physicians acknowledging TBE as a severe disease were less frequently promoting TBE vaccine among high-risk groups. These results may appear as inconsistent, or even openly in opposition with the basic assumption that a better understanding of the risk associated with a certain disorder will ultimately increase the acceptance of countermeasures [ 22 , 28 ], but it should be stressed that with an overall annual incidence of 0.1 cases/100,000 people, TBE remains an uncommon event for the majority of professionals not working in high-risk areas [ 1 , 2 , 3 , 4 , 5 ]. Previous studies on KAP of Italian OP have shown significant knowledge gaps and misunderstandings on up-to-date vaccinology [ 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, Occupational Physicians acknowledging TBE as a severe disease were less frequently promoting TBE vaccine among high-risk groups. These results may appear as inconsistent, or even openly in opposition with the basic assumption that a better understanding of the risk associated with a certain disorder will ultimately increase the acceptance of countermeasures [ 22 , 28 ], but it should be stressed that with an overall annual incidence of 0.1 cases/100,000 people, TBE remains an uncommon event for the majority of professionals not working in high-risk areas [ 1 , 2 , 3 , 4 , 5 ]. Previous studies on KAP of Italian OP have shown significant knowledge gaps and misunderstandings on up-to-date vaccinology [ 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tick-borne encephalitis (TBE) is a potentially lethal vaccine-preventable infection of the central nervous system (CNS) caused by an arbovirus (TBE virus, or TBEV) included within the Flavivirus genus, Flaviviridae family [ 1 ]. Overall incidence rates for TBE in most Western European countries have ranged between 0.4 and 0.6/100,000 over the years 2011–2015; but notification rates in certain areas (e.g., Czech Republic, Estonia, Lithuania, Slovenia) have largely exceeded 5 cases/100,000 population/years [ 2 , 3 , 4 , 5 ]. With mortality rates up to 2% and long-term neurological complications in around 10% of patients, TBE has emerged as an increasing cause of morbidity and mortality [ 1 , 2 , 3 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations